Amino or amidine-based porous polymers, methods of making and using the same

CN117534866BActive Publication Date: 2026-11-03CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210919306.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-08-02
Publication Date
2026-11-03
Estimated Expiration
2042-08-02

AI Technical Summary

Technical Problem

Existing adsorption materials are costly and polluting when treating complexed heavy metal ions, and the recovery process of heavy metal ions is complicated, making it difficult to achieve efficient and environmentally friendly adsorption and desorption cycles.

Method used

Amino- or amidine-based porous polymers are used to prepare the polymers via a salt template method. The complexed heavy metal ions are adsorbed by protonation of the amino or amidine nitrogen under CO2 gas stimulation, and then desorbed by N2 gas purging or heating treatment, thus realizing the recovery of the complexed heavy metal ions.

Benefits of technology

It achieves efficient adsorption and desorption cycle of complexed heavy metal ions, is environmentally friendly and pollution-free, and avoids the generation of strong acid or high salt wastewater, which has important environmental significance and economic value.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application discloses an amido or amidino porous polymer and a preparation method and application thereof. The preparation method comprises the following steps: mixing an amido or amidino polymer, an organic solvent I, a crosslinking agent and an inorganic salt to obtain a mixed polymer solution; then, the mixed polymer solution is divided into ball molds for crosslinking to obtain polymer small balls; and then, the polymer small balls are immersed in pure water for drying to obtain the amido or amidino porous polymer. The amido or amidino porous polymer prepared by the method can realize adsorption and desorption recovery of complex heavy metal ions, and the method is simple, green and environment-friendly.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of wastewater treatment technology, and relates to an amino- or amidine-based porous polymer, its preparation method and application, and particularly to a method for preparing an amino- or amidine-based porous polymer and its application in the enrichment and recovery of complexed heavy metal ions. Background Technology

[0002] Heavy metal ions are typical pollutants in wastewater, most of which are toxic and cannot be biodegraded. Their accumulation through the food chain can harm the balance of ecosystems and human health. Therefore, the separation of heavy metal ions is a key concern in the field of wastewater treatment. It is worth noting that heavy metal ions readily complex with EDTA, citrate, or other organic anions, significantly enhancing their migration and transformation capabilities in water bodies and increasing the difficulty of their treatment.

[0003] Methods for treating heavy metal ions in wastewater include chemical precipitation, adsorption, electrochemical methods, ion exchange, and membrane separation. These methods are relatively effective at removing free heavy metal ions; however, their efficiency in removing complexed heavy metal ions is relatively limited. Conventional treatment methods, such as chemical precipitation, often fail to achieve compliant discharge of complexed heavy metals. Studies have shown that anion exchange resins or polyamine chelating adsorbents are commonly used for the adsorption and removal of complexed heavy metal ions, offering advantages such as ease of operation, cost-effectiveness, high efficiency, and recyclability.

[0004] From a resource utilization perspective, heavy metal ions are also valuable resources. Achieving effective recovery while separating them would have significant environmental and economic benefits. However, after existing adsorption materials reach saturation with complexed heavy metal ions, strong acids or concentrated salt solutions are typically needed to desorb the complexed heavy metal ions and regenerate the adsorption material. (Lingchen, Li Pinghai, Wei Mengmeng, et al. Selective Removal of Cu from Copper Pyrophosphate Plating Cleaning Wastewater by Novel Polyamine Resin) 2+ The properties of [J]. Ion Exchange and Adsorption, 2019, 35(05): 450-460.) et al. applied their independently developed polyamine resin PAMC to the complexation of Cu with pyrophosphate. 2+ The adsorption and removal of Cu was achieved using 12% sulfuric acid. 2+ The desorption of copper and nickel ions and the regeneration of the ion exchange resins were investigated. Su Yue (Su Yue. Experimental Study on Ion Exchange Treatment of Copper-Nickel Plating Wastewater [D]. Harbin Engineering University, 2020.) selected three ion exchange resins, 732, CH-90, and D001, for the treatment of copper-nickel plating wastewater. The desorption of copper and nickel ions and the regeneration of the ion exchange resins depended on a 5% NaCl solution. The above process produces a large amount of strong acid and concentrated salt wastewater as byproducts, leading to secondary pollution and making the resource recovery of heavy ions relatively complex.

[0005] Therefore, there is an urgent need to develop a new type of adsorption material to achieve the adsorption and desorption cycle of complexed heavy metal ions in a simple, efficient, green and environmentally friendly manner. This is of great significance for the treatment of wastewater containing complexed heavy metal ions and the resource recovery of heavy metal ions. Summary of the Invention

[0006] To address the problems of high cost, significant pollution, and complex heavy metal ion recovery processes in existing adsorption methods for treating complexed heavy metal ions in wastewater, this invention provides an amino- or amidine-based porous polymer, its preparation method, and its applications. The amino- or amidine-based porous polymer prepared by this method can achieve the adsorption and desorption recovery of complexed heavy metal ions; the method is simple and environmentally friendly.

[0007] The first aspect of this invention provides a method for preparing an amino- or amidine-based porous polymer, comprising the following steps: (1) An amino or amidine polymer, organic solvent I, a crosslinking agent and an inorganic salt are mixed to obtain a mixed polymer solution; (2) The mixed polymer solution obtained in step (1) is dispensed into a spherical mold and cross-linked to obtain polymer microspheres; (3) The polymer microspheres obtained in step (2) are impregnated with pure water and dried to obtain the amino or amidine porous polymer.

[0008] In the above technical solution, in step (1), the mass fraction of the polymer in the mixed polymer solution is 5%-30%, the mass ratio of the crosslinking agent to the polymer is 1:200-1:50, and the mass ratio of the inorganic salt to the polymer is 2:1-10:1. The volume of the organic solvent I, based on the mass of the polymer, is 3~20 mL / g.

[0009] In the above technical solution, in step (1), the inorganic salt is selected from one of sodium chloride, sodium sulfate, and calcium chloride.

[0010] In the above technical solution, in step (1), the amino or amidopolymer is selected from at least one of poly(diethylaminoethyl methacrylate), poly(dimethylaminoethyl methacrylate), polyamide-amine, poly(N-vinylcaprolactam) or poly(1H-imidazol-4-yl)methyl acrylate.

[0011] In the above technical solution, in step (1), the organic solvent I is selected from one or more of ethanol, methanol, isopropanol and tert-butanol.

[0012] In the above technical solution, in step (1), the crosslinking agent is selected from one or more of polyethylene glycol, glyoxal, and trimethylolpropane.

[0013] In the above technical solution, in step (2), the diameter of the spherical mold is 0.5-2cm.

[0014] In the above technical solution, in step (2), the crosslinking temperature is 80-120℃ and the time is 8-12h. The crosslinking reaction can be carried out in a forced-air drying oven.

[0015] In the above technical solution, the soaking time in step (3) is 4-8 hours.

[0016] In the above technical solution, the drying conditions in step (3) are: drying at 50-70℃ for 4-6 hours. The drying process can be carried out in a forced-air drying oven.

[0017] In the above technical solution, in step (1), the amino or amidine polymer is prepared by free radical polymerization or polycondensation. The specific operation steps are as follows: mix the amino or amidine polymer monomer and organic solvent II, pass an inert gas (such as nitrogen) for 10-30 min, then add an initiator, place it in an oil bath at 40-90℃ or a water bath at 0-25℃, and react under an inert atmosphere (such as nitrogen) for 4-24 h, then stop the gas flow to end the reaction; add dichloromethane to dilute (1.5-3 times) the reaction solution, add the diluted reaction solution to 1-5 times the volume of n-hexane to precipitate, filter, repeat the dissolution-filtration 2-4 times, place it in a forced-air drying oven at 40-80℃ for 4-12 h to obtain the amino or amidine polymer.

[0018] In the above technical solution, the amino or amidopolymer monomer is selected from at least one of diethylaminoethyl methacrylate, dimethylaminoethyl methacrylate, methyl acrylate and ethylenediamine, N-vinylcaprolactam or methyl 3(1H-imidazol-4-yl)acrylate.

[0019] In the above technical solution, the organic solvent II is selected from at least one of 1,4-dioxane, dimethylformamide, toluene, or methanol; the initiator is selected from at least one of azobisisobutyronitrile, benzoyl peroxide, or dicumyl peroxide.

[0020] In the above technical solution, the mass ratio of the amino or amidine polymerizing monomer to the initiator is 2000:1-100:1; the volume of the organic solvent II is 0.6-5 mL / g based on the mass of the polymerizing monomer.

[0021] A second aspect of the present invention provides an amino or amidine porous polymer obtained according to any of the preparation methods described in the first aspect.

[0022] A third aspect of the present invention provides a method for using the amino or amidine porous polymers described in the second aspect to enrich and recover complexed heavy metal ions, comprising the following steps: (a) The above-mentioned amine or amidine porous polymer after CO2 gas purging is added to wastewater containing complexed heavy metal ions, and the complexed heavy metal ions are enriched on the polymer surface by stirring and adsorption. (b) The amine or amidine porous polymers that have adsorbed complexed heavy metal ions are purged with N2 gas or dried by heating, and the complexed heavy metal ions are desorbed, thereby realizing the recovery of complexed heavy metal ions.

[0023] As a further technical solution to the method of enriching and recovering complexed heavy metal ions with amine or amidine porous polymers, the adsorption characteristics of the amine or amidine porous polymers can be restored. Specifically, the amine or amidine porous polymers are purged with CO2 gas to protonate the amine or amidine groups in the material, thereby restoring the adsorption characteristics of the amine or amidine porous polymer material, which is then applied to the next adsorption-desorption cycle.

[0024] In the above technical solution, in step (a), the complexed heavy metal ions include [Cu(EDTA)]. 2- [Ni(EDTA)] 2- [Cd(EDTA)] 2- [Pb(EDTA)] 2- [Zn(EDTA)] 2- [Cu(CA)] - [Ni(CA)] - [Cd(CA)] - [Pb(CA)] - [Zn(CA)] - [Cu(DPA)] 2- [Ni(DPA)] 2- [Cd(DPA)] 2- [Pb(DPA)] 2- Or [Zn(DPA)] 2- At least one of the following, wherein EDTA represents ethylenediaminetetraacetic acid, CA represents citrate, and DPA represents pyrophosphate.

[0025] In the above technical solution, in step (a), the ratio of the amount of the amino- or amidine-based porous polymer added to the concentration (content) of the complexed heavy metal ions is 2-200.

[0026] In the above technical solution, in step (a), the adsorption stirring rate is 200-600 rpm and the stirring time is 0.5-2 h.

[0027] In the above technical solution, in step (a), relative to 100 mg of amino or amidine porous polymer material, the CO2 purge gas flow rate is 100-300 mL / min, and the purge time is 5-20 min.

[0028] In the above technical solution, in step (b), relative to 100 mg of amino- or amidine-based porous polymer material, the N2 purging gas flow rate is 100-300 mL / min, and the purging time is 1-2 h.

[0029] In the above technical solution, in step (b), the drying temperature is 60-80℃ and the drying time is 30-60min.

[0030] Compared with the prior art, the present invention has the following beneficial effects: 1. This invention uses a salt template method to prepare an amino- or amidine-based porous polymer material. The preparation method is simple, low-cost, environmentally friendly, and efficient, making it easy to produce and promote.

[0031] 2. In this invention, the amino nitrogen or amidine nitrogen in the amino or amidine porous polymer undergoes protonation under CO2 gas stimulation, and the complexed heavy metal ions are adsorbed onto the material surface by electrostatic attraction. Through N2 gas purging or heat treatment, the complexed heavy metal ions spontaneously desorb from the material surface, further enabling the recovery of these ions. Using N2 gas purging or heat treatment as the method for recovering complexed heavy metal ions and CO2 gas purging as the method for material regeneration is environmentally friendly and efficient, and can also serve as a means of CO2 gas absorption and reuse.

[0032] 3. The amino- or amidine-based porous polymers prepared by the method of this invention are used for the separation and recovery of complexed heavy metal ions in wastewater. This method is clean and environmentally friendly, causing no damage to the material itself or the wastewater system, and effectively avoiding the generation of strong acid or high-salt wastewater, thus preventing secondary pollution. While achieving the purification effect of wastewater contaminated with complexed heavy metal ions, it also realizes the effective recovery of resources, possessing significant environmental and economic value. Detailed Implementation

[0033] The preparation method of amino- or amidine-based porous polymers and their application in the separation and recovery of complexed heavy metal ions are described in more detail below through specific examples. These examples are merely illustrative of specific implementations of the method of the present invention and do not constitute a limitation on the scope of protection of the present invention.

[0034] Unless otherwise specified, the experimental methods used in the following examples are conventional methods in the art. Unless otherwise specified, the experimental materials used in the following examples were purchased from conventional biochemical reagent stores.

[0035] Determination of complexed heavy metal ion concentration: The concentration of complexed heavy metal ions in the wastewater was determined using an inductively coupled plasma optical emission spectrometer (iCAP 6300, Thermo Scientific). The adsorption removal efficiency was calculated based on the concentration of complexed heavy metal ions before and after the adsorption process, and the desorption recovery efficiency was calculated based on the concentration of complexed heavy metal ions before and after the desorption process. The calculation formulas are shown below: ; Where A% represents the adsorption removal efficiency, and C... A,0 and C A The concentration of complexed heavy metal ions before and after adsorption is given by C, where D% represents the desorption recovery efficiency. D,0 and C D The concentration of complexed heavy metal ions before and after desorption. Example 1

[0036] Synthesis of amine or amidine polymers: Diethylaminoethyl methacrylate (7.5 g) and 1,4-dioxane (10 mL) were added to a reaction flask and mixed thoroughly under magnetic stirring, with high-purity nitrogen purging during the process. After nitrogen purging for 30 min, the initiator azobisisobutyronitrile (7.5 mg) was added, and the mixture was placed in an 80°C oil bath and reacted under nitrogen protection for 4 h. After the reaction was completed, the nitrogen purging was stopped, and the reaction flask was opened to the atmosphere to terminate the polymerization reaction. After the reaction flask cooled to room temperature, the 1,4-dioxane solvent in the reaction system was removed using a rotary evaporator, and 5 mL of dichloromethane was added to the reaction flask to dissolve the reaction product. The reaction product solution was added dropwise to 20 mL of n-hexane to precipitate the product, filtered, and the dissolution-filtration process was repeated once. The resulting product was poly(diethylaminoethyl methacrylate), which was dried in a vacuum drying oven at 60°C for 4 h.

[0037] Synthesis of porous amine or amidine polymers: Dissolve 2g of the obtained poly(diethylaminoethyl methacrylate) in 20mL of ethanol, add 20mg of polyethylene glycol and 10g of sodium chloride granules, and stir to obtain a mixed polymer solution. Dispense the obtained polymer solution into spherical molds with a diameter of 1cm, and place them in a forced-air drying oven at 100℃ for 8h to crosslink, obtaining polymer microspheres. Remove the obtained polymer microspheres from the spherical molds and immerse them in pure water for 6h, then place them in a forced-air drying oven at 60℃ for 6h to obtain porous poly(diethylaminoethyl methacrylate).

[0038] Porous poly(diethylaminoethyl methacrylate) is used for the separation and recovery of complexed heavy metal ions: Add porous poly(diethylaminoethyl methacrylate) (1 g / L) to 100 mL of [Cu(EDTA)].2- Wastewater with a concentration of 50 mg / L was treated with CO2 gas purging at a flow rate of 200 mL / min for 10 min. The mixture was stirred and adsorbed at 300 rpm for 1 h. The [Cu(EDTA)] in the wastewater was then measured. 2- The residual concentration was calculated, and the effect of porous poly(diethylaminoethyl methacrylate) on [Cu(EDTA)] was obtained. 2- The adsorption removal efficiency was 96%. Porous poly(diethylaminoethyl methacrylate) adsorbed with complexed heavy metal ions was placed in 10 mL of pure water and purged with N2 gas at a flow rate of 300 mL / min for 1 h. The concentration of heavy metal ions in the pure water was measured, and the adsorption efficiency of porous poly(diethylaminoethyl methacrylate) for [Cu(EDTA)] was calculated. 2- The desorption and recovery efficiency is 85%.

[0039] Furthermore, porous poly(diethylaminoethyl methacrylate) was purged with CO2 gas and applied to [Cu(EDTA)]. 2- The adsorption-desorption cycle was repeated 5 times. In these 5 adsorption-desorption cycles, porous poly(diethylaminoethyl methacrylate) reacted with [Cu(EDTA)]. 2- The adsorption and removal efficiencies of [Cu(EDTA)] remained at 95%–99%. 2- The desorption and recovery efficiency remained at 80%~95%. Example 2

[0040] Synthesis of amine or amidine polymers: 10 g of dimethylaminoethyl methacrylate and 10 mL of dimethylformamide were added to a reaction flask and mixed thoroughly under magnetic stirring, with high-purity nitrogen purging during the process. After nitrogen purging for 10 min, benzoyl peroxide (20 mg) was added as an initiator, and the flask was placed in a 50 °C oil bath and reacted under nitrogen protection for 24 h. After the reaction was completed, the nitrogen purging was stopped, and the reaction flask was opened to the atmosphere to terminate the polymerization reaction. After the reaction flask cooled to room temperature, the dimethylformamide solvent in the reaction system was removed by rotary evaporation, and 10 mL of dichloromethane was added to the reaction flask to dissolve the reaction product. The reaction product solution was added dropwise to 40 mL of n-hexane to precipitate the product, filtered, and the dissolution-filtration process was repeated twice to obtain poly(dimethylaminoethyl methacrylate), which was then dried in a 50 °C vacuum drying oven for 8 h.

[0041] Synthesis of porous amine or amidine polymers: Dissolve 4g of the obtained poly(dimethylaminoethyl methacrylate) in 20mL of isopropanol, add 20mg of glyoxal and 8g of sodium sulfate granules, and stir to obtain a mixed polymer solution. Dispense the obtained polymer solution into spherical molds with a diameter of 0.5cm, and place them in a forced-air drying oven at 90℃ for 10h to obtain polymer microspheres. Remove the obtained polymer microspheres from the spherical molds and immerse them in pure water for 4h, then place them in a forced-air drying oven at 50℃ for 4h to obtain porous poly(dimethylaminoethyl methacrylate).

[0042] Porous poly(dimethylaminoethyl methacrylate) is used for the separation and recovery of complexed heavy metal ions: Add porous poly(dimethylaminoethyl methacrylate) (1 g / L) to 100 mL of [Ni(EDTA)]. 2- In wastewater with a concentration of 20 mg / L, CO2 gas purging was performed at a flow rate of 100 mL / min for 20 min. The mixture was stirred and adsorbed at 200 rpm for 0.5 h. The [Ni(EDTA)] in the wastewater was then measured. 2- The residual concentration was calculated, and the effect of porous poly(dimethylaminoethyl methacrylate) on [Ni(EDTA)] was obtained. 2- The adsorption removal efficiency was 99%. Porous poly(dimethylaminoethyl methacrylate) adsorbed with complexed heavy metal ions was placed in 10 mL of pure water and purged with N2 gas at a flow rate of 100 mL / min for 2 h. The concentration of heavy metal ions in the pure water was measured, and the adsorption efficiency of porous poly(dimethylaminoethyl methacrylate) on [Ni(EDTA)] was calculated. 2- The desorption and recovery efficiency is 87%.

[0043] Furthermore, porous poly(dimethylaminoethyl methacrylate) was purged with CO2 gas and applied to [Ni(EDTA)]. 2- The adsorption-desorption cycle was repeated 5 times. In these 5 adsorption-desorption cycles, porous poly(dimethylaminoethyl methacrylate) reacted with [Ni(EDTA)]. 2- The adsorption and removal efficiencies of [Ni(EDTA)] remained between 96% and 99%. 2- The desorption and recovery efficiency remained at 85% to 95%. Example 3

[0044] Synthesis of amine or amidine polymers: Ethylenediamine (4.66 g) and methanol (25 mL) were added to a reaction flask and mixed thoroughly under magnetic stirring. The mixture was placed in an ice-water bath at 0°C, and high-purity nitrogen was purged during this process. After nitrogen purging for 20 min, methyl acrylate (5.34 g) was added dropwise using a constant-pressure funnel. After the addition was complete, the reaction was stirred in the ice-water bath for another 2 h. Then, the mixture was transferred to a water bath at 25°C and reacted for another 18 h under nitrogen protection. After the reaction was completed, the nitrogen purging was stopped, and the reaction flask was opened to the atmosphere to terminate the polymerization reaction. After the reaction flask cooled to room temperature, the methanol solvent in the reaction system was removed using a rotary evaporator, and 25 mL of dichloromethane was added to the reaction flask to dissolve the reaction product. The reaction product solution was then added dropwise to 50 mL of n-hexane to precipitate the product. The mixture was filtered, and the dissolution-filtration process was repeated three times to obtain the polyamide-amine, which was dried in a vacuum drying oven at 70°C for 8 h.

[0045] Synthesis of porous amine or amidine polymers: Dissolve 3g of the obtained polyamide-amine in 20mL of methanol, add 60mg of trimethylolethane and 21g of calcium chloride granules, and stir to obtain a mixed polymer solution. Dispense the obtained polymer solution into spherical molds with a diameter of 1.5cm, and place them in a forced-air drying oven at 80℃ for 8h to crosslink, obtaining polymer microspheres. Remove the obtained polymer microspheres from the spherical molds and immerse them in pure water for 8h, then place them in a forced-air drying oven at 50℃ for 5h to obtain porous polyamide-amine.

[0046] Porous polyamide-amine for the separation and recovery of complexed heavy metal ions: Add porous polyamide-amine (1 g / L) to 100 mL of [Cu(CA)] - In wastewater with a concentration of 10 mg / L, CO2 gas purging was performed at a flow rate of 200 mL / min for 10 min. The mixture was stirred and adsorbed at 400 rpm for 1.5 h. The [Cu(CA)] in the wastewater was then measured. - The residual concentration was then used to calculate the ratio of porous polyamide-amine to [Cu(CA)]. - The adsorption removal efficiency was 99%. The porous polyamide-amine, which adsorbed complexed heavy metal ions, was placed in a 60℃ drying oven for 60 min. The concentration of heavy metal ions in pure water was measured, and the effect of porous polyamide-amine on [Cu(CA)] was calculated. - The desorption and recovery efficiency is 86%.

[0047] Furthermore, the porous polyamide-amine was purged with CO2 gas and applied to [Cu(CA)]. -The adsorption-desorption cycle was repeated 5 times. In these 5 adsorption-desorption cycles, the porous polyamide-amine [Cu(CA)]... - The adsorption and removal efficiencies of [Cu(CA)] remained between 95% and 99%. - The desorption and recovery efficiencies remained at 85% to 99%. Example 4

[0048] Synthesis of amine or amidine polymers: N-vinylcaprolactam (4g) and toluene (10mL) were added to a reaction flask and mixed thoroughly under magnetic stirring, with high-purity nitrogen purging during the process. After nitrogen purging for 30 minutes, dicumyl peroxide (2mg) was added as an initiator, and the flask was placed in an 80℃ oil bath and reacted under nitrogen protection for 16 hours. After the reaction was completed, nitrogen purging was stopped, and the reaction flask was opened to the atmosphere to terminate the polymerization reaction. After the reaction flask cooled to room temperature, toluene solvent in the reaction system was removed by rotary evaporation, and 20mL of dichloromethane was added to the reaction flask to dissolve the reaction product. The reaction product solution was added dropwise to 90mL of n-hexane to precipitate, filtered, and the dissolution-filtration process was repeated twice to obtain poly-N-vinylcaprolactam, which was dried in an 80℃ vacuum drying oven for 12 hours.

[0049] Synthesis of porous amine or amidine polymers: Dissolve 5g of the obtained poly-N-vinylcaprolactam in 20mL of tert-butanol, add 25mg of polyethylene glycol and 50g of sodium chloride granules, and stir to obtain a mixed polymer solution. Dispense the obtained polymer solution into spherical molds with a diameter of 2cm, and place them in a forced-air drying oven at 110℃ for 10h to obtain polymer microspheres. Remove the obtained polymer microspheres from the spherical molds and immerse them in pure water for 6h, then place them in a forced-air drying oven at 70℃ for 6h to obtain porous poly-N-vinylcaprolactam.

[0050] Porous poly-N-vinylcaprolactam for the separation and recovery of complexed heavy metal ions: Add porous poly(N-vinylcaprolactam) (1 g / L) to 100 mL of [Pb(DPA)]. 2- Wastewater with a concentration of 50 mg / L was treated with CO2 gas purging at a flow rate of 300 mL / min for 5 min. The mixture was stirred and adsorbed at 500 rpm for 2 h. The [Pb(DPA)] in the wastewater was then determined. 2- The residual concentration was then used to calculate the p-value of porous poly(N-vinylcaprolactam) for [Pb(DPA)]. 2-The adsorption removal efficiency was 95%. Porous poly(N-vinylcaprolactam) containing adsorbed complexed heavy metal ions was placed in 10 mL of pure water and purged with N2 gas at a flow rate of 200 mL / min for 1.5 h. The concentration of heavy metal ions in the pure water was measured, and the adsorption efficiency of porous poly(N-vinylcaprolactam) on [Pb(DPA)] was calculated. 2- The desorption and recovery efficiency is 85%.

[0051] Furthermore, porous poly(N-vinylcaprolactam) was purged with CO2 gas and applied to [Pb(DPA)]. 2- The adsorption-desorption cycle was repeated 5 times. In these 5 adsorption-desorption cycles, the porous poly(N-vinylcaprolactam) showed [Pb(DPA)]... 2- The adsorption and removal efficiencies of [Pb(DPA)] remained between 95% and 98%. 2- The desorption and recovery efficiency remained at 80% to 90%. Example 5

[0052] Synthesis of amine or amidine polymers: 2.5 g of 3-(1H-imidazol-4-yl)methyl acrylate and 10 mL of 1,4-dioxane were added to a reaction flask and mixed thoroughly under magnetic stirring, with high-purity nitrogen purging during the process. After nitrogen purging for 30 min, 2.5 mg of azobisisobutyronitrile (AIB) initiator was added, and the mixture was placed in a 90 °C oil bath and reacted under nitrogen protection for 10 h. After the reaction was completed, nitrogen purging was stopped, and the reaction flask was opened to the atmosphere to terminate the polymerization reaction. After the reaction flask cooled to room temperature, the 1,4-dioxane solvent in the reaction system was removed by rotary evaporation, and 15 mL of dichloromethane was added to the reaction flask to dissolve the reaction product. The reaction product solution was added dropwise to 100 mL of n-hexane to precipitate the product, filtered, and the dissolution-filtration process was repeated twice to obtain poly(1H-imidazol-4-yl)methyl acrylate, which was then dried in a 60 °C vacuum drying oven for 12 h.

[0053] Synthesis of porous amine or amidine polymers: Dissolve 2g of the obtained poly(1H-imidazol-4-yl) methyl acrylate in 20mL of ethanol, add 20mg of polyethylene glycol and 10g of sodium chloride granules, and stir to obtain a mixed polymer solution. Dispense the obtained polymer solution into spherical molds with a diameter of 1cm, and place them in a forced-air drying oven at 120℃ for 10h to obtain polymer microspheres. Remove the obtained polymer microspheres from the spherical molds and immerse them in pure water for 8h, then place them in a forced-air drying oven at 60℃ for 6h to obtain porous poly(1H-imidazol-4-yl) methyl acrylate.

[0054] Porous poly(1H-imidazol-4-yl)methyl acrylate is used for the separation and recovery of complexed heavy metal ions: Add porous poly(1H-imidazol-4-yl)methyl acrylate (1 g / L) to 100 mL of [Zn(DPA)]. 2- In wastewater with a concentration of 5 mg / L, CO2 gas purging was performed at a flow rate of 200 mL / min for 10 min. The mixture was stirred and adsorbed at 600 rpm for 0.5 h. The [Zn(DPA)] in the wastewater was then measured. 2- The residual concentration was calculated, and the relationship between porous poly(1H-imidazol-4-yl)methyl acrylate and [Zn(DPA)] was obtained accordingly. 2- The adsorption removal efficiency was 99%. Porous poly(1H-imidazol-4-yl)methyl acrylate with adsorbed complexed heavy metal ions was placed in an 80℃ drying oven for 40 min. The concentration of heavy metal ions in pure water was measured, and the effect of porous poly(1H-imidazol-4-yl)methyl acrylate on [Zn(DPA)] was calculated. 2- The desorption and recovery efficiency is 90%.

[0055] Furthermore, porous poly(1H-imidazol-4-yl)methyl acrylate was purged with CO2 gas and applied to [Zn(DPA)]. 2- The adsorption-desorption cycle was repeated 5 times. In these 5 adsorption-desorption cycles, porous poly(1H-imidazolium-4-yl)methyl acrylate was effective against [Zn(DPA)]. 2- The adsorption and removal efficiencies of [Zn(DPA)] remained at 97%~99%. 2- The desorption and recovery efficiency remained at 90%~99%. Comparative Example 1

[0056] Synthesis of porous amine or amidine polymers: Polyvinyl alcohol (2g) and NaCl (5g) were dissolved in 100mL of deionized water to form a continuous aqueous phase, which was added to the reaction flask. Diethylaminoethyl methacrylate (7.5g), toluene (10mL), and ethylene glycol dimethacrylate (150mg) were mixed to form a dispersed oil phase, which was added to the reaction flask. The two phases were thoroughly dispersed under magnetic stirring, and high-purity nitrogen was introduced during this process. After continuous nitrogen purging for 30 minutes, the initiator azobisisobutyronitrile (7.5mg) was added, and the mixture was placed in an 80℃ oil bath and reacted for 4 hours under nitrogen protection. After the reaction was completed, the nitrogen flow was stopped, and the reaction flask was opened to the atmosphere to terminate the polymerization reaction. The reaction solution was filtered, and the resulting solid was washed with water and air-dried to obtain porous poly(diethylaminoethyl methacrylate).

[0057] Porous poly(diethylaminoethyl methacrylate) is used for the separation and recovery of complexed heavy metal ions: Add porous poly(diethylaminoethyl methacrylate) (1 g / L) to 100 mL of [Cu(EDTA)]. 2- Wastewater with a concentration of 50 mg / L was treated with CO2 gas purging at a flow rate of 200 mL / min for 10 min. The mixture was stirred and adsorbed at 300 rpm for 1 h. The [Cu(EDTA)] in the wastewater was then measured. 2- The residual concentration was calculated, and the effect of porous poly(diethylaminoethyl methacrylate) on [Cu(EDTA)] was obtained. 2- The adsorption removal efficiency was 56%. Porous poly(diethylaminoethyl methacrylate) adsorbed with complexed heavy metal ions was placed in 10 mL of pure water and purged with N2 gas at a flow rate of 300 mL / min for 1 h. The concentration of heavy metal ions in the pure water was measured, and the adsorption efficiency of porous poly(diethylaminoethyl methacrylate) for [Cu(EDTA)] was calculated. 2- The desorption and recovery efficiency is 65%.

[0058] Furthermore, porous poly(diethylaminoethyl methacrylate) was purged with CO2 gas and applied to [Cu(EDTA)]. 2- The adsorption-desorption cycle was repeated 5 times. In these 5 adsorption-desorption cycles, porous poly(diethylaminoethyl methacrylate) reacted with [Cu(EDTA)]. 2- The adsorption and removal efficiencies of [Cu(EDTA)] remained between 50% and 70%. 2- The desorption and recovery efficiencies remained at 55% to 75%. Comparative Example 2

[0059] Synthesis of amine or amidine polymers: Diethylaminoethyl methacrylate (7.5 g) and 1,4-dioxane (10 mL) were added to a reaction flask and mixed thoroughly under magnetic stirring, with high-purity nitrogen purging during the process. After nitrogen purging for 30 min, the initiator azobisisobutyronitrile (7.5 mg) was added, and the mixture was placed in an 80°C oil bath and reacted under nitrogen protection for 4 h. After the reaction was completed, the nitrogen purging was stopped, and the reaction flask was opened to the atmosphere to terminate the polymerization reaction. After the reaction flask cooled to room temperature, the 1,4-dioxane solvent in the reaction system was removed using a rotary evaporator, and 5 mL of dichloromethane was added to the reaction flask to dissolve the reaction product. The reaction product solution was added dropwise to 20 mL of n-hexane to precipitate the product, filtered, and the dissolution-filtration process was repeated once. The resulting product was poly(diethylaminoethyl methacrylate), which was dried in a vacuum drying oven at 60°C for 4 h.

[0060] Synthesis of porous amine or amidine polymers: Dissolve 2g of the obtained poly(diethylaminoethyl methacrylate) in 20mL of ethanol, add 20mg of polyethylene glycol and 10g of sodium chloride granules, and stir to obtain a mixed polymer solution. Dispense the obtained polymer solution into spherical molds with a diameter of 1cm, and place them in a forced-air drying oven at 35℃ for 12h to obtain polymer microspheres. Remove the obtained polymer microspheres from the spherical molds and immerse them in pure water for 6h, then place them in a forced-air drying oven at 60℃ for 6h to obtain porous poly(diethylaminoethyl methacrylate).

[0061] Porous poly(diethylaminoethyl methacrylate) is used for the separation and recovery of complexed heavy metal ions: Add porous poly(diethylaminoethyl methacrylate) (1 g / L) to 100 mL of [Cu(EDTA)]. 2- Wastewater with a concentration of 50 mg / L was treated with CO2 gas purging at a flow rate of 200 mL / min for 10 min. The mixture was stirred and adsorbed at 300 rpm for 1 h. The [Cu(EDTA)] in the wastewater was then measured. 2- The residual concentration was calculated, and the effect of porous poly(diethylaminoethyl methacrylate) on [Cu(EDTA)] was obtained. 2- The adsorption removal efficiency was 82%. Porous poly(diethylaminoethyl methacrylate) adsorbed with complexed heavy metal ions was placed in 10 mL of pure water and purged with N2 gas at a flow rate of 300 mL / min for 1 h. The concentration of heavy metal ions in the pure water was measured, and the adsorption efficiency of porous poly(diethylaminoethyl methacrylate) for [Cu(EDTA)] was calculated. 2- The desorption and recovery efficiency is 75%.

[0062] Furthermore, porous poly(diethylaminoethyl methacrylate) was purged with CO2 gas and applied to [Cu(EDTA)]. 2- The adsorption-desorption cycle was repeated 5 times. In these 5 adsorption-desorption cycles, porous poly(diethylaminoethyl methacrylate) reacted with [Cu(EDTA)]. 2- The adsorption and removal efficiencies of [Cu(EDTA)] remained at 80%–90%. 2- The desorption and recovery efficiency remained at 70% to 80%. Comparative Example 3

[0063] Synthesis of amine or amidine polymers: Diethylaminoethyl methacrylate (7.5 g) and 1,4-dioxane (10 mL) were added to a reaction flask and mixed thoroughly under magnetic stirring, with high-purity nitrogen purging during the process. After nitrogen purging for 30 min, the initiator azobisisobutyronitrile (7.5 mg) was added, and the mixture was placed in an 80°C oil bath and reacted under nitrogen protection for 4 h. After the reaction was completed, the nitrogen purging was stopped, and the reaction flask was opened to the atmosphere to terminate the polymerization reaction. After the reaction flask cooled to room temperature, the 1,4-dioxane solvent in the reaction system was removed using a rotary evaporator, and 5 mL of dichloromethane was added to the reaction flask to dissolve the reaction product. The reaction product solution was added dropwise to 20 mL of n-hexane to precipitate the product, filtered, and the dissolution-filtration process was repeated once. The resulting product was poly(diethylaminoethyl methacrylate), which was dried in a vacuum drying oven at 60°C for 4 h.

[0064] Synthesis of porous amine or amidine polymers: Dissolve 2g of the obtained poly(diethylaminoethyl methacrylate) in 20mL of ethanol, add 20mg of polyethylene glycol and 10g of sodium chloride granules, and stir to obtain a mixed polymer solution. Dispense the obtained polymer solution into spherical molds with a diameter of 1cm, and place them in a forced-air drying oven at 100℃ for 8h to crosslink, obtaining polymer microspheres. Remove the obtained polymer microspheres from the spherical molds and immerse them in pure water for 6h, then place them in a forced-air drying oven at 60℃ for 6h to obtain porous poly(diethylaminoethyl methacrylate).

[0065] Porous poly(diethylaminoethyl methacrylate) is used for the separation and recovery of metal ions. Add porous poly(diethylaminoethyl methacrylate) (1 g / L) to 100 mL of Cu 2+ In wastewater with a concentration of 50 mg / L, adsorption was performed by stirring at 300 rpm for 1 hour, and the Cu in the wastewater was determined. 2+ The residual concentration of porous poly(diethylaminoethyl methacrylate) for Cu was calculated from this. 2+ The adsorption removal efficiency was 96%. The amine-based porous polymer adsorbed with metal ions was placed in 10 mL of pure water and purged with CO2 gas. The CO2 gas flow rate was controlled at 200 mL / min, and the purging time was 10 min. The concentration of metal ions in the pure water was measured, and the adsorption efficiency of porous poly(diethylaminoethyl methacrylate) for Cu was calculated. 2+ The desorption and recovery efficiency is 92%.

[0066] Furthermore, porous poly(diethylaminoethyl methacrylate) was purged with N2 gas at a flow rate of 300 mL / min for 1 h, and then applied to Cu. 2+The next adsorption-desorption cycle was repeated 5 times. In the 5-cycle adsorption-desorption experiment, porous poly(diethylaminoethyl methacrylate) was used to treat Cu. 2+ The adsorption and removal efficiencies of Cu were all maintained at 95%~98%. 2+ The desorption and recovery efficiency remained at 90%~98%.

Claims

1. A method for preparing an amino or amidine porous polymer, comprising the following steps: (1) An amino or amidine polymer, organic solvent I, a crosslinking agent and an inorganic salt are mixed to obtain a mixed polymer solution; (2) The mixed polymer solution obtained in step (1) is dispensed into a spherical mold and cross-linked to obtain polymer microspheres; (3) The polymer microspheres obtained in step (2) are impregnated with pure water and dried to obtain the amino or amidine porous polymer; In step (1), the amino or amidine polymer is selected from at least one of poly(diethylaminoethyl methacrylate), poly(dimethylaminoethyl methacrylate), polyamide-amine, poly(N-vinylcaprolactam), or poly(1H-imidazol-4-yl)methyl acrylate; the solvent I is selected from one or more of ethanol, methanol, isopropanol, and tert-butanol; and the crosslinking agent is selected from one or more of polyethylene glycol, glyoxal, and trimethylolethane. In step (2), the crosslinking temperature is 80-120℃ and the crosslinking time is 8-12h.

2. The manufacturing method according to claim 1, characterized in that, In step (1), the mass fraction of polymer in the mixed polymer solution is 5%-30%, the mass ratio of crosslinking agent to polymer is 1:200-1:50, the mass ratio of inorganic salt to polymer is 2:1-10:1, and the volume of organic solvent I is 3~20 mL / g based on the mass of polymer.

3. The manufacturing method according to claim 1, characterized in that, In step (1), the inorganic salt is selected from sodium chloride, sodium sulfate, and calcium chloride.

4. The manufacturing method according to claim 1, characterized in that, In step (3), the soaking time is 4-8 hours.

5. The amino or amidine porous polymer obtained by the method according to any one of claims 1-4.

6. A method for using the amino or amidine porous polymer according to claim 5 to enrich and recover complexed heavy metal ions, comprising the following steps: (a) Add the amine or amidine porous polymer after CO2 gas purging to the wastewater containing complexed heavy metal ions, and achieve the enrichment of complexed heavy metal ions on the polymer surface by stirring and adsorption. (b) The amine or amidine porous polymers that have adsorbed complexed heavy metal ions are purged with N2 gas or dried by heating, and the complexed heavy metal ions are desorbed, thereby realizing the recovery of complexed heavy metal ions.

7. The method according to claim 6, characterized in that, In step (a), the complexed heavy metal ions include [Cu(EDTA)]. 2- [Ni(EDTA)] 2- [Cd(EDTA)] 2- [Pb(EDTA)] 2- [Zn(EDTA)] 2- [Cu(CA)] - [Ni(CA)] - [Cd(CA)] - [Pb(CA)] - [Zn(CA)] - [Cu(DPA)] 2- [Ni(DPA)] 2- [Cd(DPA)] 2- [Pb(DPA)] 2- Or [Zn(DPA)] 2- At least one of them.

8. The method according to claim 6, characterized in that, In step (a), the ratio of the amount of the amino- or amidine-based porous polymer added to the mass concentration of the complexed heavy metal ions is 2-200.

9. The method according to claim 6, characterized in that, In step (a), the adsorption stirring rate is 200-600 rpm and the stirring time is 0.5-2 h.

10. The method according to claim 6, characterized in that, In step (a), the CO2 purge gas flow rate is 100-300 mL / min relative to 100 mg of amino or amidine porous polymer material, and the purge time is 5-20 min.

11. The method according to claim 6, characterized in that, In step (b), the N2 purge gas flow rate is 100-300 mL / min relative to 100 mg of amine or amidine porous polymer material, and the purge time is 1-2 h.

12. The method according to claim 6, characterized in that, In step (b), the drying temperature is 60-80℃ and the drying time is 30-60min.

Citation Information

Patent Citations

  • Organic porous polymer material and synthetic method thereof

    CN101954273A

  • Carbon dioxide responsive polyvinylidene fluoride blended membrane and preparation method thereof

    CN106178988A